SURIMI BASED DRIED FISH CAKE - BASU, SUBRATA (Journal of Indian Fisheries Association, 2015)
Minced fish prepared from the fillets of the sciaenid fish (Lutjanus sp.) was washed with cold water (<10 Â°C) three times. The washed muscle was pressed through a piece of fine cloth to a moisture content around 80%. The pressed cake (Surimi) was ground with 2.5% sodium chloride and 3% tapioca starch. The mixed material was shaped in the form of a cake and left for one hour for the gel to set. The cakes were then steamed. The cooled cakes were cut into pieces of 1 cm length x 1 cm width x 0.5 cm thick. The pieces were either dried in an electrical oven at 50Â°C or dried in sun to a moisture content of 11-12%. Biochemical, bacteriological and organoleptic evaluation revealed that the cakes were in very good acceptable form for 8 months. The cakes could be rehydrated by soaking in water at ambient temperature for half an hour and boiling in water for 10 minutes.